A Comparison of Selected Bibliographic Database Search Retrieval for Agricultural Information - Ritchie, Stephanie; Banyas, Kelly; Sevin, Carol (Issues in Science and Technology Librarianship, 2019)
Search result retrieval was compared across eight research literature databases (AGRICOLA, AGRIS, BIOSIS, CAB Direct, FSTA, Google Scholar, Scopus, and Web of Science) for three topics from different agricultural disciplines to compare retrieval results based on searcher experience. Precision, recall, and uniqueness were analyzed by rating search results ( 2400 citations) for relevancy. A generalized linear model statistical analysis determined that AGRICOLA ranked highest for precision and was statistically more likely to produce a relevant result than four other databases. CAB and Web of Science ranked highest for recall and both overlapped with AGRICOLA for statistical likelihood of producing a relevant result. Google Scholar retrieved the most unique content, but almost half of that content was not judged relevant. AGRICOLA, BIOSIS and CAB retrieved the most unique and relevant content. This study will help researchers and librarians working in the agricultural disciplines to select the bibliographic databases that will provide the most relevant search results and are most likely to meet their research need. It may also serve as a template for future bibliographic research in other disciplines.